Carbon policy in a high-growth economy: The case of China - Lucas Bretschger; Lin Zhang (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
There is widespread concern that an international agreement on stringent climate policies will not be reached because it would imply too high costs for fast growing economies like China. To quantify these costs we develop a general equilibrium model with fully endogenous growth. The framework includes disaggregated industrial and energy sectors, endogenous innovation, and sector-specific investments. We find that the implementation of Chinese government carbon policies until 2020 causes a welfare reduction of 0.3 percent. For the long run up to 2050 we show that welfare costs of internationally coordinated emission reduction targets lie between 3 and 8 percent. Assuming faster energy technology development, stronger induced innovation, and rising energy prices in the reference case reduces welfare losses significantly. We argue that increased urbanization raises the costs of carbon policies due to altered consumption patterns.
Keywords: Q54; O41; O53; C68; 330; Carbon policy; China; Endogenous growth; Induced innova- tion; Urbanization; Internationale Umweltpolitik; Soziale Kosten; Wirtschaftswachstum; Innovation; Urbanisierung; Allgemeines Gleichgewicht; Endogenes Wachstumsmodell; China